2001
DOI: 10.4049/jimmunol.167.8.4329
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Signaling Defect of Lyn-Sequestering, Signal-Curtailing FcεRI Dimers: Aggregated Dimers Can Dissociate from Lyn and Form Signaling Complexes with Syk

Abstract: Clustering the tetrameric (αβγ2) IgE receptor, FcεRI, on basophils and mast cells activates the Src-family tyrosine kinase, Lyn, which phosphorylates FcεRI β and γ subunit tyrosines, creating binding sites for the recruitment and activation of Syk. We reported previously that FcεRI dimers formed by a particular anti-FcεRI α mAb (H10) initiate signaling through Lyn activation and FcεRI subunit phosphorylation, but cause only modest activation of Syk and little Ca2+ mobilization and secretion. Curtailed signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…4. study. Although the likelihood of this possibility seems to be strengthened by data showing that the aggregated H10 mAb induced activation comparable in extent to multivalent Ag [9], our own unpublished data render this explanation unlikely because the removal of aggregates by ultracentrifugation did not alter the properties of the mAb. Furthermore, confocal microscopy revealed an almost homogeneous distribution of the H10 mAb on cells incubated with the Ab for 5 min before fixation and staining (not shown).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…4. study. Although the likelihood of this possibility seems to be strengthened by data showing that the aggregated H10 mAb induced activation comparable in extent to multivalent Ag [9], our own unpublished data render this explanation unlikely because the removal of aggregates by ultracentrifugation did not alter the properties of the mAb. Furthermore, confocal microscopy revealed an almost homogeneous distribution of the H10 mAb on cells incubated with the Ab for 5 min before fixation and staining (not shown).…”
Section: Discussionmentioning
confidence: 92%
“…These complexes are relatively stable and are not rapidly internalized, as suggested by the absence of an increased amount of clathrin-coated pits in the vicinity of Fc 4 RI dimers/oligomers (see also [9]). How these small complexes are internalized remains to be solved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multichain Fc receptors, such as FcεRI, FcαRI, FcγRI and FcγRIII have been known to initiate cell signaling following interactions with multivalent ligands that induce their clustering. 35,62,63,132,140,163,[169][170][171][172][173][238][239][240][241] FcεRI aggregates as small as dimers have been reported to be capable of providing an effective activation signal to cause mediator secretion. 163 Using a set of chemically well-defined ligands of valences 1-3, the magnitude of the cellular response has been demonstrated to dramatically increase as the valency of a ligand raises from two to three.…”
Section: Supportive Evidence For the School Model Of Multichain Recepmentioning
confidence: 99%
“…Clearly, the strength of the ligand determines not only duration of the ligand-MIRR contact but also lifetime of an individual receptor in the engaged MIRR thus suggesting the importance of the orientational restraint in ligand-specific FceRI dimers/oligomers for generating competent activation signal. 163,164,171,178,179,261 Further, in the IgA receptor, FcαRI, a positively charged arginine residue within the TM domain of ligand recognition α chain promotes association with the signaling FcRγ chain. 153 Studies of signaling through mutants of the FcαRI have shown that a vertical relocation of this TM positive charge does not have any significant effect on proximal and distal receptor functions, whereas a lateral transfer of the positive charge completely abrogates these functions.…”
mentioning
confidence: 99%